2022
DOI: 10.3390/cells11223551
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Cancer and Cardiovascular Disease

Abstract: Although cardiac tumor formation is rare, accumulating evidence suggests that the two leading causes of deaths, cancers, and cardiovascular diseases are similar in terms of pathogenesis, including angiogenesis, immune responses, and fibrosis. These similarities have led to the creation of new exciting field of study called cardio-oncology. Here, we review the similarities between cancer and cardiovascular disease from the perspective of microRNAs (miRNAs). As miRNAs are well-known regulators of translation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 158 publications
0
15
0
Order By: Relevance
“…[1][2][3] Aberrant expression of miRNAs is highly correlated with the development and progression of various types of human malignancies, and the quantication of the miRNA expressing level is signicant in cancer detection, staging, progression, and response to therapies. 4,5 For instance, alterations in the miRNA-21 expression level have a signicant effect on carcinogenesis and can function as an oncogenic gene in gastric carcinoma, a devastating illness with far-reaching consequences for world health. 6,7 The precise identication and quantitative determination of miRNAs are crucial for the clinical diagnosis and treatment of disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Aberrant expression of miRNAs is highly correlated with the development and progression of various types of human malignancies, and the quantication of the miRNA expressing level is signicant in cancer detection, staging, progression, and response to therapies. 4,5 For instance, alterations in the miRNA-21 expression level have a signicant effect on carcinogenesis and can function as an oncogenic gene in gastric carcinoma, a devastating illness with far-reaching consequences for world health. 6,7 The precise identication and quantitative determination of miRNAs are crucial for the clinical diagnosis and treatment of disease.…”
Section: Introductionmentioning
confidence: 99%
“…As a class of small molecular RNA, MicroRNA has the length of approximately 20–25 nucleotides. Through binding to the 3′ non‐coding region of the target gene mRNA, microRNA can cause the inhibition or degradation of the target mRNA, leading to gene silencing, and thus participating in a series of vital processes containing tumor proliferation, invasion and migration 19 . A series of evidences have indicated that miRNAs are abnormally expressed in the development of osteosarcoma, providing strong evidence for understanding the pathogenesis of osteosarcoma and diagnosis of osteosarcoma 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Through binding to the 3 0 noncoding region of the target gene mRNA, microRNA can cause the inhibition or degradation of the target mRNA, leading to gene silencing, and thus participating in a series of vital processes containing tumor proliferation, invasion and migration. 19 A series of evidences have indicated that miRNAs are abnormally expressed in the development of osteosarcoma, providing strong evidence for understanding the pathogenesis of osteosarcoma and diagnosis of osteosarcoma. 20,21 In addition, miRNAs may affect the development and progression of osteosarcoma by the regulation of signaling pathways including PI3K/ Akt, Notch, RAS/P21, MAPK, Wnt, and Jun/FOS signaling pathways.…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) can play the role of oncogenes or cancer suppressor genes in various types of human cancer. [9][10][11] miR-455-3p was under-expressed in various tumors and can be involved in adjusting diverse biological processes, containing cell proliferation, apoptosis, migration, and drug resistance, as a tumor suppressor gene. [12][13][14][15] According to previous studies, miR-455-3p inhibited PCa cell growth through targeted regulation of eIF4E.…”
Section: Introductionmentioning
confidence: 99%